2019
DOI: 10.15283/ijsc18101
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Injecting Adipose-Derived Stromal Vascular Fraction Cells to Accelerate Microcirculation in Ischemic Diabetic Feet: A Pilot Study

Abstract: Background and Objectives Beneficial effects of human adipose-derived stromal vascular fraction (SVF) cell injection on microcirculation have been recently reported in in vitro and in vivo studies. However, no clinical studies have reported its effect in diabetic patients who commonly experience compromised tissue perfusion, regardless of the status of intravascular blood flow. The present piloting study was designed to clinically examine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Their use helped the emergence of a near-natural skin concept in terms of appearance, texture, color, and metabolic properties. Other investigations have used autologous or allogenic ADSCs in the treatment of Crohn's disease, critical limb ischemia, diabetic foot ulcers, and burns [63,[79][80][81][82]. In combination with fat or platelet-rich lysate, skin engraftment, and reconstitution have been improved in human and animal models [83][84][85].…”
Section: Adscs Advancements In Skin Therapymentioning
confidence: 99%
“…Their use helped the emergence of a near-natural skin concept in terms of appearance, texture, color, and metabolic properties. Other investigations have used autologous or allogenic ADSCs in the treatment of Crohn's disease, critical limb ischemia, diabetic foot ulcers, and burns [63,[79][80][81][82]. In combination with fat or platelet-rich lysate, skin engraftment, and reconstitution have been improved in human and animal models [83][84][85].…”
Section: Adscs Advancements In Skin Therapymentioning
confidence: 99%
“…It has been used for clinic treatment of various conditions and shown good safety and healing effects. Moon and colleagues injected SVF cells into the affected area of diabetic foot patients, and the microvascular blood flow of the wound surface was found significantly increased with no adverse reactions [ 11 , 12 ]. Studies found that SVF could secrete a variety of cytokines, differentiate into various cells such as endothelial cells, and have the potential to participate in angiogenesis in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that subcutaneous transplantation of ASC sheet prepared from non-diabetic mice into diabetic mice improved glucose intolerance ( Ishida et al, 2020 ). Subcutaneous injection and local administration of human adipose-derived stromal vascular fraction cells showed a beneficial effect on microcirculation in ischemic diabetic feet and wound healing ( Nie et al, 2011 ; Moon et al, 2019 ). Moreover, its application in tissue engineering and fat grafting in reconstructive surgery is being extensively explored ( Naderi et al, 2014 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%